2019
DOI: 10.3889/oamjms.2019.252
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Platelet–To-Lymphocyte Ratio in Prostate Cancer

Abstract: BACKGROUND: Previous studies demonstrated the promising value of platelet-to-lymphocyte (PLR) in prostate cancer. AIM: This study was conducted to evaluate its pre-biopsy values in predicting prostate cancer. METHODS: We included all benign prostatic hyperplasia (BPH) and prostate cancer (PCa) patients who underwent a prostate biopsy in Adam Malik Hospital between August 11th 2011 and August 31st 2015. The relationship between pre-biopsy variables which could be affecting the percentage of prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…Recently, various blood parameters (NLR, PLR, LMR, and MPV) [8,9,10,11,12,13] have been utilized to predict the diagnosis of PCa, clinically signi cant PCa, and its outcomes. However using these blood parameters is still a matter of debate and controversial as different studies argued that they are unreliable in detecting PCa [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, various blood parameters (NLR, PLR, LMR, and MPV) [8,9,10,11,12,13] have been utilized to predict the diagnosis of PCa, clinically signi cant PCa, and its outcomes. However using these blood parameters is still a matter of debate and controversial as different studies argued that they are unreliable in detecting PCa [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In Korean patients with gray-zone PSA, NLR was associated with PCa detection and GS ≥ 4 + 3 cancer [11]. Adhyatma et al discovered that prebiopsy PLR is valuable in detecting PCa [12]. Mehmet et al reported that aggressive PCa is associated with NLR increase; however, they suggested that prostatitis limited the use of NLR in detecting PCa [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But a prospective study found that the neutrophil/lymphocyte ratio did not discriminate between benign and malignant prostatic disease in patients with a PSA between 4-10 ng/ml [19]. A retrospective study by Adhyatma KP et al found that PLR gives promising value in predicting prostate cancer in suspected patients [20]. A retrospective study by Kaynar M et al found that statistically signi cant differences were observed in the mean PLR values only if the PSA level was 10 ng/ml and above in the BPH and PCa groups [21].…”
Section: Discussionmentioning
confidence: 99%
“…14 Urokinase plasminogen activation (uPA and uPAR) is involved in PCa progression, however it seems to be helpful in predicting poor pathologic characteristics rather than diagnosis of PCa. 15 There have also been a number of studies about the diagnostic role of the platelet-to-lymphocyte ratio (PLR) [16][17][18][19] ; the neutrophil-to-lymphocyte ratio (NLR) 20 and the combined use of PSA, mean platelet volume (MPV), and platelet distribution width (PDW). 21 These studies found these values to be associated with a poor prognosis in PCa patients.…”
Section: Discussionmentioning
confidence: 99%